AI CHATBOTS’ ROLE IN ASSISTING ENGLISH LITERATURE STUDENTS’ WRITING SKILL - Nisak, Khoirotun; Ishlahiyah, Mazroatul (Annual International Conferences on Language, Literature, and Media, 2023)
Technological advancements in the digital era necessitate the present generation to adapt and coexist with these changes. It is vital to acknowledge these current advancements. Numerous scholarly investigations have been conducted on artificial intelligence, encompassing various areas such as robots and Chat bots. This study focused on using Chat bots AI in writing, making it very interesting using cognitivism theory by George Siemens. This study's main objective was to discover the role of an AI Chatbot and its progressive and regressive impacts on student perspectives. More specifically, this study investigated a sample of 32 participants who were English Literature students in their fourth semester. These individuals have utilized Chatbots AI platforms, like Chat GPT and other similar Chatbots, as aids for their writing assignments. They were requested to complete a previously administered online survey. The findings indicated that AI Chatbots are significant in completing writing assignments. These platforms serve as sources of inspiration, aid in comprehending complex subjects, and effectively assist in restructuring sentences. Moreover, the consequence is heightened temporal efficacy for students in accomplishing academic tasks. In other hand, there is also a significant addictive tendency.